2020
DOI: 10.1126/science.abc2399
|View full text |Cite
|
Sign up to set email alerts
|

A thalamocortical top-down circuit for associative memory

Abstract: The sensory neocortex is a critical substrate for memory. Despite its strong connection with the thalamus, the role of direct thalamocortical communication in memory remains elusive. We performed chronic in vivo two-photon calcium imaging of thalamic synapses in mouse auditory cortex layer 1, a major locus of cortical associations. Combined with optogenetics, viral tracing, whole-cell recording, and computational modeling, we find that the higher-order thalamus is required for associative learning and transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 42 publications
3
89
2
Order By: Relevance
“…Importantly, the fact that L1 cINs have been shown to receive both thalamic (Ji, Zingg et al 2015) and inter-cortical connections (Leinweber, Ward et al 2017) ideally positions them to modulate incoming sensory inputs and affect excitatory responses (Zhu and Zhu 2004, Jiang, Wang et al 2013, Lee, Wang et al 2015, Anastasiades, Collins et al 2020). L1 cINs have been shown to play a role in, cross-modal integration (Ibrahim, Mesik et al 2016), interhemispheric integration (Palmer, Schulz et al 2012), associative fear learning and plasticity (Abs, Poorthuis et al 2018, Pardi, Vogenstahl et al 2020) as well as sensory motor integration (Mesik, Huang et al 2019). This makes L1 cINs a likely important target for the integration of bottom-up and top-down signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the fact that L1 cINs have been shown to receive both thalamic (Ji, Zingg et al 2015) and inter-cortical connections (Leinweber, Ward et al 2017) ideally positions them to modulate incoming sensory inputs and affect excitatory responses (Zhu and Zhu 2004, Jiang, Wang et al 2013, Lee, Wang et al 2015, Anastasiades, Collins et al 2020). L1 cINs have been shown to play a role in, cross-modal integration (Ibrahim, Mesik et al 2016), interhemispheric integration (Palmer, Schulz et al 2012), associative fear learning and plasticity (Abs, Poorthuis et al 2018, Pardi, Vogenstahl et al 2020) as well as sensory motor integration (Mesik, Huang et al 2019). This makes L1 cINs a likely important target for the integration of bottom-up and top-down signaling.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no direct evidence that such transthalamic top-down, modulatory pathways exist. Evidence exists that higher order thalamic nuclei provide modulator inputs to first order, primary cortical areas in visual (Purushothaman et al, 2012 ; Roth et al, 2016 ), somatosensory (Viaene et al, 2011 ) and auditory systems (Pardi et al, 2020 ). Because modulation is provided by a higher order thalamic nucleus to a lower order cortical area, these circuits can be viewed as descending, top-down circuits.…”
Section: L5 Corticothalamic Projections Initiate Transthalamic Corticocortical Pathwaysmentioning
confidence: 99%
“…Because modulation is provided by a higher order thalamic nucleus to a lower order cortical area, these circuits can be viewed as descending, top-down circuits. Using a combination of optogenetics, whole-cell recordings, behavior, and computational modeling, Pardi et al ( 2020 ) identified an auditory top-down circuit that conveys information about the experience-dependent behavioral relevance of sounds from higher order auditory thalamus (all nuclei surrounding the MGV) to layer 1 in primary auditory cortex (anatomical evidence for this pathway in classical studies: Lorente de No, 1938 ; Malmierca et al, 2002 ). Interestingly, synaptic transmission in A1 is in turn modulated by local inhibition acting on GABAB receptors at the presynaptic thalamic terminal.…”
Section: L5 Corticothalamic Projections Initiate Transthalamic Corticocortical Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations